Rap1‐mediated nucleosome displacement can regulate gene expression in senescent cells without impacting the pace of senescence. Issue 1 (19th November 2019) - Song, Shufei; Perez, Javier V.; Svitko, William; Ricketts, M. Daniel; Dean, Elliot; Schultz, David; Marmorstein, Ronen; Johnson, F. Brad
Abstract: Cell senescence is accompanied, and in part mediated, by changes in chromatin, including histone losses, but underlying mechanisms are not well understood. We reported previously that during yeast cell senescence driven by telomere shortening, the telomeric protein Rap1 plays a major role in reprogramming gene expression by relocalizing hundreds of new target genes (called NRTS, for n ew R ap1 t argets at s enescence) to the promoters. This leads to two types of histone loss: Rap1 lowers histone level globally by repressing histone gene expression, and it also causes local nucleosome displacement at the promoters of upregulated NRTS. Here, we present evidence of direct binding between Rap1 and histone H3/H4 heterotetramers, and map amino acids involved in the interaction within the Rap1 SANT domain to amino acids 392–394 (SHY). Introduction of a point mutation within the native RAP1 locus that converts these residues to alanines ( RAP1 SHY ), and thus disrupts Rap1‐H3/H4 interaction, does not interfere with Rap1 relocalization to NRTS at senescence, but prevents full nucleosome displacement and gene upregulation, indicating direct Rap1‐H3/H4 contacts are involved in nucleosome displacement. Consistent with this, the histone H3/H4 chaperone Asf1 is similarly unnecessary for Rap1 localization to NRTS but is required for full Rap1‐mediated nucleosome displacement and gene activation. Remarkably, RAP1 SHY does not affect the pace of senescence‐related cell cycle arrest, indicating that some changes in gene expression at senescence are not coupled to this arrest. Abstract : Rap1 interacts directly with histones to displace nucleosomes at the promoters of upregulated genes at senescence. A mutation that perturbs Rap1‐histone interactions leads to compromised nucleosome loss and blunted gene activation, but no change is observed in the rate of senescence. Our findings shed light on mechanisms of Rap1‐mediated gene expression changes at senescence and show that these can be uncoupled from the pace of senescence.